Preparation, in Vitro Anti-inflammatory Activity and Structural Characterization of Acipenser schrenckii Milt Peptide - LIU Wenbo, ZHAO Qing, LI Hailan, LIAO Tao, ZU Xiaoyan (Shipin Kexue)
The aim of this study was to investigate the anti-inflammatory potential and molecular properties of sturgeon (Acipenser schrenckii) milt peptide (SMP). SMP was obtained from alkali-extracted protein from sturgeon milt by enzymatic hydrolysis and purification, and its inhibitory effect on nitric oxide (NO) and bovine serum albumin (BSA) denaturation was evaluated. Then, the molecular mass, secondary structure, crystalline structure, proton peak distribution and amino acid sequence were determined by various spectroscopies, and based on the obtained results, the anti-inflammatory activity of amino acid sequences was predicted. The results showed that at a concentration of 10 mg/mL, SMP inhibited NO and BSA degradation by 45.33% and 60.34%, respectively, which was significantly more effective than sturgeon milt protein (P < 0.05). Basic and hydrophobic amino acids accounted for 37.45% and 36.77% the total amino acids of SMP, respectively, with arginine accounting for the highest proportion (16.28%). The molecular masses of SMP were concentrated in the range of 206–1 040 Da, which mainly showed an irregular amorphous structure and exposed more hydrophobic groups in aqueous solution. SMP contained many short peptides, including MPY, YWH, YPY and VPPL, and these peptide sequences had anti-inflammatory properties. In summary, SMP has potential anti-inflammatory activity and possesses the potential for further development and application as a promising source of natural anti-inflammatory peptides.